Convenience Yield, Inflation Expectations, and Public Debt Growth - Fu, Julie Zhiyu; Li, Jian; Xie, Yinxi (Review of Financial Studies, 2025)
Abstract We present new facts on how convenience yields fluctuate with macroeconomic variables and fiscal policy: the convenience yield of long-term Treasuries is negatively correlated with inflation expectations, and inflation expectations predict future debt-to-GDP growth. To rationalize these findings, we incorporate the convenience yield into a macro-finance model with endogenous fiscal policy. The government finances deficit shocks partially through higher inflation and partially through more future borrowing, which reduces the convenience yield today. The feedback loop between the convenience yield and future debt supply amplifies the effect of fiscal shocks. We further verify this channel using empirically constructed exogenous deficit shocks.